Analisis Faktor-Faktor yang Berhubungan terhadap Keselamatan di Tempat Kerja pada PT. X Semasa Pandemi COVID-19 - Hartono, Muhammad Faqih; Lestari, Fatma (National Journal of Occupational Health and Safety, 2023)
PT X Unit Citeureup is the largest cement manufacturing industrial plant in the world. The industrial processes in PT X Unit Citeureup involve a variety of processes, materials, and hazardous works. Thus, the work process in it causes a lot of occupational safety and health risks. In addition, at this time PT X Unit Citeureup is also facing the challenges of the COVID-19 pandemic just like other industries. This situation can have a negative impact on both employees and management of PT X Unit Citeureup. Based on this situation, the establishment of safety in the workplace is something that must be pursued and maximized. This study attempts to evaluate the factors that shape workplace safety with COVID-19 prevention measures and the dimensions of occupational health and safety (OHS) vulnerability. These dimensions can be used as the basis for the study of elements of organizational psychology and safety climate that are able to predict safety in the workplace. This research was conducted through a quantitative approach with a cross-sectional study design. Data collection is done online via google form to find out how workers perceive related to the variables studied. Data collection was carried out in May with a large sample of 126 respondents from 19 divisions. The next data were analyzed by PLS-SEM (Partial Least Square Structural Equation Modeling). The results of this study indicate that OHS vulnerability factors such as OHS awareness and OHS participation as well as COVID-19 prevention measures are significantly related to safety in the workplace. These results indicate that interventions to increase OHS awareness, OHS participation, and COVID-19 prevention measures in the workplace can improve workplace safety during the COVID-19 pandemic.